Strengthening Active Physical Education Learning Through a PJOK Trofeo Program: a Service-Learning Approach with Pre-Service Teachers at SD Citra Bakti - Nikodemus Bate; Bernabas Wani; Josep Marsianus Rewo; Yanuarius Ricardus Natal; Agustina Meo; Yohanes Paulus De Brito Naru (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
This community service program aimed to enhance active learning and sportsmanship in elementary physical education through the implementation of a structured PJOK Trofeo model supported by pre-service teachers (PLP students). Conducted at SD Citra Bakti, the program adopted a service-learning framework integrating collaborative mentoring among lecturers, pre-service teachers, and school teachers. The intervention was implemented in four stages: needs assessment, collaborative design, structured Trofeo-based activities, and reflective evaluation. Data were collected using observation sheets assessing student participation and sportsmanship indicators, complemented by reflective reports from pre-service teachers. The results demonstrated a significant increase in active participation (from 62% to 85%) and improvements in sportsmanship indicators, including fair play and teamwork. Furthermore, pre-service teachers showed enhanced pedagogical competence in classroom management and active learning facilitation. The novelty of this program lies in reconstructing a competitive format into a pedagogical device that integrates cooperative learning principles and service learning within a community-based partnership. This model provides a replicable framework for character-oriented and experiential physical education practices.